Representasi Krisis Identitas Gender Pasca Operasi Kelamin (Studi Tentang Detransitioner di Kanal Youtube Blaire White) - Fahrudin, Atef; Wulandari, Ajeng Ayu (Universitas Al Azhar Indonesia, 2025)
This study examines the representation of post-surgical gender identity crisis in Blaire White's YouTube channel through the narrative of detransitioner